MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA SMP DENGAN MODEL PEMBELAJARAN THINK TALK WRITE - Astrid Chandra Sari (Journal of Mathematics Education and Science, 2018)
The purpose of this research are to know whether the average problem solving abilities matematis of students who were taught using Think Talk write learning model can achieve exhaustiveness learning and whether the average problem solving abilities matematis of students who were taught using Think Talk write learning model are better than average the average problem solving ability of students who were taught using the learning model of konvensional. The population in this research is VII grade students of SMP N 1 Klambu. By random sampling technique obtained two classes as a research sample, namely class VIIC as the experimental class and class VII B as the control class. The data was collected by the documentation methods, test methods and observation methods. Based on the analysis of research results is known that 83,3% of students who were taught using Think Talk write learning model can achieve exhaustiveness learning. In addition, there are significant differences between the average problem solving abilities matematis of students who were taught using the learning model of Think Talk write with students who are taught using the learning model of konvensional. From the above description it can be concluded that the application of Think Talk write learning model is effective towards problem solving ability matematis of VII grade students of SMP N 1 Klambu at the material quadrilateral. Penelitian ini bertujuan untuk mengetahui apakah rata-rata kemampuan pemecahan masalah matematis siswa yang diajar menggunakan model pembelajaran Think Talk write dapat mencapai ketuntasan belajar dan apakah rata-rata kemampuan pemecahan masalah matematis siswa yang diajar menggunakan model pembelajaran Think Talk write lebih baik daripada rata-rata kemampuan pemecahan masalah matematis siswa yang diajar menggunakan model pembelajaran konvensional. Populasi dalam penelitian ini adalah peserta didik kelas VII SMP N 1 Klambu. Dengan teknik random sampling diperoleh dua kelas sebagai sampel penelitian yaitu kelas VII C sebagai kelas eksperimen dan kelas VII B sebagai kelas kontrol. Pengumpulan data dilakukan dengan metode dokumentasi, metode tes dan metode observasi. Berdasarkan analisis hasil penelitian diketahui bahwa 83,3% siswa yang diajar menggunakan model pembelajaran Think Talk write mencapai ketuntasan belajar. Selain itu, terdapat perbedaan yang signifikan antara rata-rata kemampuan pemecahan masalah matematis siswa yang diajar menggunakan model pembelajaran Think Talk write dengan siswa yang diajar menggunakan model pembelajaran konvensional. Dari uraian di atas dapat disimpulkan bahwa penerapan model pembelajaran Think Talk write efektif terhadap kemampuan pemecahan masalah matematis siswa kelas VII SMP N 1 Klambu pada materi segiempat.